2017
DOI: 10.3390/rs9060520
|View full text |Cite
|
Sign up to set email alerts
|

Recent Deceleration of the Ice Elevation Change of Ecology Glacier (King George Island, Antarctica)

Abstract: Abstract:Glacier change studies in the Antarctic Peninsula region, despite their importance for global sea level rise, are commonly restricted to the investigation of frontal position changes. Here we present a long term (37 years; 1979-2016) study of ice elevation changes of the Ecology Glacier, King George Island (62 • 11 S, 58 • 29 W). The glacier covers an area of 5.21 km 2 and is located close to the H. Arctowski Polish Antarctic Station, and therefore has been an object of various multidisciplinary studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 63 publications
8
58
0
Order By: Relevance
“…The first field studies of glaciers in Admiralty Bay were conducted in the 1950s and reported a general reduction in ice extent [7]. Since the 1950s, an increased glacier retreat has been reported on King George Island by numerous studies [6,[8][9][10][11][12]]. An increase in surface temperature was also observed over the past several years.…”
Section: Characterization Of the Research Areamentioning
confidence: 91%
“…The first field studies of glaciers in Admiralty Bay were conducted in the 1950s and reported a general reduction in ice extent [7]. Since the 1950s, an increased glacier retreat has been reported on King George Island by numerous studies [6,[8][9][10][11][12]]. An increase in surface temperature was also observed over the past several years.…”
Section: Characterization Of the Research Areamentioning
confidence: 91%
“…of the cross-validation residuals obtained from the interpolation of the annual surface mass-balance grids. The determined uncertainty in annual surface mass balance should be considered a lower bound Engel and others: Surface mass balance of small glaciers on James Ross Island, north-eastern Antarctic Peninsula, during [2009][2010][2011][2012][2013][2014][2015] because local variations in the snow thickness are not addressed. The uncertainty in cumulative surface mass balance is calculated as the std dev.…”
Section: Error Estimationmentioning
confidence: 99%
“…Engel and others: Surface mass balance of small glaciers on James Ross Island, north-eastern Antarctic Peninsula, during [2009][2010][2011][2012][2013][2014][2015] the first decade of the 21st century, as indicated by the glaciological data from different parts of the northern AP including JRI (Davies and others, 2012;Navarro and others, 2013). The period of mass loss terminated in the mass-balance year 2008/09, after which the glaciers in the northern AP experienced a shift to mostly positive mass balances (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Reynolds and Froude numbers are also presented for both creeks (Figure 2a,b). The period of the field campaign was characterized by higher air temperatures relative to other summer months over the last decade [49,50,53]. The mean monthly air temperature was +1.0 • C in January and +1.1 • C in February for the period from 2007 to 2016 [54].…”
Section: Study Sitementioning
confidence: 99%